A stock flow ecological model from a Latin American perspective - Lorenzo Nalin; Leonardo Rojas Rodriguez; Esteban Pérez Caldentey; José Eduardo Alatorre; Giuliano Toshiro Yajima (Levy Economics Institute of Bard College, 2023)
This study aims to develop an ecological stock-flow consistent (SFC) model based on the Latin American-stylized facts regarding economic, financial, and environmental features. We combine the macro-financial theoretical framework by Pérez-Caldentey et al. (2021, 2023) and the ecological modeling of Carnevali et al. (2020) and Dafermos et al. (2018). We discuss two scenarios that test exogenous climate-related shocks. The first scenario presents the case in which international regulation on commodity trade becomes more stringent due to environmental concerns, thus worsening the balance-of-payment constraint of the region. The second scenario concerns the increase in frequency and intensity of adverse climate events in the region. Both scenarios show that the financial external constraint that determines the growth path of Latin American economies may be further exacerbated due to environmental-related issues.
Keywords: Q54; Q43; E12; N16; 330; Climate Change; Energy Transition; Stock Flow Models; Latin America